Association between being Overweight in Young Childhood and during School Age and Puberty - Genki Shinoda; Yudai Nagaoka; Fumihiko Ueno; Naoyuki Kurokawa; Ippei Takahashi; Tomomi Onuma; Aoi Noda; Keiko Murakami; Mami Ishikuro; Taku Obara; Hirohito Metoki; Junichi Sugawara; et al. (MDPI AG, 2023)
To examine whether body type at birth, body weight, and obesity in early childhood are associated with overweight/obesity during school age and puberty. Data from maternal and child health handbooks, baby health checkup information, and school physical examination information of participants at birth and three-generation cohort studies were linked. Association between body type and body weight at different time intervals (at birth and at 1.5, 3.5, 6, 11, and 14 years of age) were comprehensively analyzed using a multivariate regression model adjusted for gender, maternal age at childbirth, maternal parity, and maternal body mass index, and drinking and smoking statuses at pregnancy confirmation. Children who are overweight in young childhood had a greater risk of being overweight. Particularly, overweight at one year of age during checkup was associated with overweight at 3.5 years (adjusted odds ratio (aOR), 13.42; 95% confidence interval (CI), 4.46-45.42), 6 years (aOR, 6.94; 95% CI, 1.64-33.46), and 11 years (aOR, 5.22; 95% CI, 1.25-24.79) of age. Therefore, being overweight in young childhood could increase the risk of being overweight and obese during school age and puberty. Early intervention in young childhood may be warranted to prevent obesity during school age and puberty.